Navigating the Impact of Overprotective Parenting on Adolescent Adaptation and Independence - Soumokil, Krislinda Valoma Fergie; Kristinawati, Wahyuni (Jurnal Bimbingan dan Konseling Terapan, 2024)
This study explores the correlation between overprotective parenting and adolescent adjustment in an Indonesian educational context, focusing specifically on SMA Negeri 1 Ambon. Utilizing a quantitative research design with correlation analysis, the study examines how adolescents aged 10-18 navigate changes during the transition from childhood, especially in terms of their adaptability and independence. The influence of familial, school, and societal environments on these developments is assessed through purposive sampling of 110 students, using scales that measure overprotective behaviors and personal adjustment. Findings from the study reveal a statistically significant but weak negative correlation between overprotective parenting and adolescent adjustment, indicating that while parental involvement is crucial, excessive control can undermine adolescents' ability to adapt to their environments effectively. This study underscores the complex dynamics between parental behavior and adolescent development, suggesting that balanced parenting is key to fostering responsible and adaptable youths.